2012
DOI: 10.1111/j.1476-5381.2012.02061.x
|View full text |Cite
|
Sign up to set email alerts
|

The selective sphingosine 1‐phosphate receptor modulator BAF312 redirects lymphocyte distribution and has species‐specific effects on heart rate

Abstract: BACKGROUND AND PURPOSEBAF312 is a next-generation sphingosine 1-phosphate (S1P) receptor modulator, selective for S1P1 and S1P5 receptors. S1P1 receptors are essential for lymphocyte egress from lymph nodes and a drug target in immune-mediated diseases. Here, we have characterized the immunomodulatory potential of BAF312 and the S1P receptor-mediated effects on heart rate using preclinical and human data.EXPERIMENTAL APPROACHBAF312 was tested in a rat experimental autoimmune encephalomyelitis (EAE) model. Elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
334
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(376 citation statements)
references
References 39 publications
(50 reference statements)
15
334
2
4
Order By: Relevance
“…However, differences in specificity and pharmacokinetics, along with a paucity of available data, make it difficult to generalize cardiac effects across compounds in this class. Data on BAF312 preclinical models and healthy subjects have shown species-specific differences in S1P receptor specificity for first dose cardiac effects [9]. A previous study has demonstrated that initiation of BAF312 at a therapeutic dose of 10 mg resulted in clinically relevant bradycardia (as determined by measurement of mean HRmin) [7].…”
Section: Tablementioning
confidence: 99%
See 2 more Smart Citations
“…However, differences in specificity and pharmacokinetics, along with a paucity of available data, make it difficult to generalize cardiac effects across compounds in this class. Data on BAF312 preclinical models and healthy subjects have shown species-specific differences in S1P receptor specificity for first dose cardiac effects [9]. A previous study has demonstrated that initiation of BAF312 at a therapeutic dose of 10 mg resulted in clinically relevant bradycardia (as determined by measurement of mean HRmin) [7].…”
Section: Tablementioning
confidence: 99%
“…The study period was a maximum of 44 days for each subject, comprising a 21-day screening period, a 12-day treatment period (days [1][2][3][4][5][6][7][8][9][10][11][12] and an end of study assessment 10 days after the last treatment day (day 22). Sub-E. Legangneux et al…”
Section: Study Period and Drug Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…7 However, clinical studies with S1P agonists with selectivity for S1P 1 over S1P 3 have suggested that in humans the heart rate reduction effects are controlled at least in part through agonism of S1P 1 . 8 Additionally, through the course of our own studies it was discovered that simply abolishing S1P 3 agonism was not sufficient to eliminate the acute and chronic pulmonary toxicity elicited in rodents by 1 or by selective S1P 1 full agonists, findings that led us to discontinue our efforts related to S1P 1 full agonists and seek alternative profiles that could overcome these liabilities. 9 In this letter we describe the identification of a differentiated S1P 1 receptor modulator, BMS-986104 (3d), which distinguishes itself from 1 in terms of cardiovascular and pulmonary safety based on preclinical pharmacology while showing equivalent efficacy in a T-cell transfer colitis model.…”
mentioning
confidence: 99%
“…16−19 However, our recent report suggested species-dependent bradycardia and a dominant role of S1P 1 in mediating heart rate in humans, as the treatment with BAF312, a dual S1P 1,5 agonist sparing S1P 3 activity, caused GIRK channel activation in human atrial myocytes and bradycardia in healthy volunteers. 20 In the same report, we presented the in vitro profile of BAF312, including its effects on S1P 1 receptor internalization as well as its preclinical efficacy in a rat experimental autoimmune encephalomyelitis (EAE) model. Herein, we report our medicinal chemistry efforts that culminated in the discovery of (E)-1-(4-(1-(((4-cyclohexyl-3-(trifluoromethyl)benzyl)oxy)-imino)ethyl)-2-ethylbenzyl)azetidine-3-carboxylic acid 32 (BAF312, Siponimod), a potent S1P 3 -sparing S1P 1 agonist currently undergoing clinical trials in patients with multiple sclerosis.…”
mentioning
confidence: 99%